2019
DOI: 10.1103/physrevb.100.060302
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous thermal expansion and chiral phonons in BiB3O6

Abstract: The origins of anomalous thermal expansion in the chiral monoclinic solid α-BiB3O6 have been studied through ab initio calculations. Positive and negative axial thermal expansion are shown to be driven by librations of borate units, elastic anisotropy, and most notably by chiral acoustic phonons involving elliptical revolutions of bismuth atoms. The chirality of the lattice gives rise to these modes by allowing the transverse acoustic branches to have opposite circular polarizations, only one of which couples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 60 publications
(127 reference statements)
1
9
0
Order By: Relevance
“…Such type of phonons was also recently observed in the transition metal dichalcogenide WSe 2 [72] and predicted to exist in a MoS 2 /WS 2 heterostructure [73]. Additionally, recent studies show the possibility of experimental realization of the chiral phonons in more complex systems like BiB 3 O 6 [74].…”
supporting
confidence: 61%
“…Such type of phonons was also recently observed in the transition metal dichalcogenide WSe 2 [72] and predicted to exist in a MoS 2 /WS 2 heterostructure [73]. Additionally, recent studies show the possibility of experimental realization of the chiral phonons in more complex systems like BiB 3 O 6 [74].…”
supporting
confidence: 61%
“…In addition, the present implementation can also be straightforwardly used to study thermal expansion within the quasi-harmonic approximation (see Ref. 97 for an example application) or electron-phonon coupling.…”
Section: B the Strain Perturbation In Density-functional Perturbatiomentioning
confidence: 99%
“…It has been shown that chiral phonons can couple with circularly polarized light and valley electrons and result in chiral selective optical transitions [10][11][12][13]. And it was proposed that chiral phonons can make important contributions to the thermal conductivity [14], phononic Hall effect [15,16], orbital magnetization [17][18][19], and anomalous thermal expansion [20]. Most recently, the concept of chiral phonons has been extended to three-dimensional (3D) systems, enabling propagating chiral phonons [21].…”
mentioning
confidence: 99%